Iranian and American Moral Judgments for Everyday Dilemmas Are Mostly Similar - Yazdanpanah, Aryan; Soltani, Sarvenaz; Mirfazeli, Fatemeh Sadat; Shariat, Seyed Vahid; Jahanbakhshi, Amin; GhaffariHosseini, Faraneh; Alavi, Kaveh; Hosseinpour, Parisa; Javadnia, Parisa; Grafman, Jordan (Frontiers in Psychology, 2021)
Moral judgment is a complex cognitive process that partly depends upon social and individual cultural values. There have been various efforts to categorize different aspects of moral judgment, but most studies depend upon rare dilemmas. We recruited 25 subjects from Tehran, Iran, to rate 150 everyday moral scenarios developed by Knutson et al. Using exploratory factor analysis (EFA), we observed that the same moral dimensions (except socialness dimension) were driven by the same moral cognitive factors (norm violation, intention, and social affect) in Iranian vs. American studies. However, there were minor differences in the factor loadings between the two cultures. Furthermore, based on the EFA results, we developed a short form of the questionnaire by removing eleven of the fifteen scenarios from each of the ten categories. These results could be used in further studies to better understand the similarities and differences in moral judgment in everyday interactions across different cultures.